HISTOLOGICAL STUDY OF HUMAN SUBLINGUAL GLAND WITH SPECIAL EMPHASIS ON INTERCALATED AND STRIATED DUCTS: Histological Study of Human Sublingual Gland - Saga, Dr Zarmina; Rana, Rehana; Minhas, Liaqat Ali; Mubarik, Azhar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To study the histomorphological characteristics of human sublingual gland, specially of intercalated and striated ducts. Study design: Descriptive study Place and duration of study: Army Medical College from Jan 2002 to Dec 2002 Materials and methods: Fifteen sublingual glands (right and left) from postmortem cases were obtained from District Headquarter Hospital Rawalpindi, within twelve hours of death. Five micrometer thick sections were made and stained with Haematoxylin and Eosin (H&E). Morphology of intercalated and striated ducts was studied and their number was counted. Results: The mean number of intercalated ducts in the right gland ―a‖ and ―b‖ parts, and in the left gland ―a‖ and ―b‖ parts was 1.45±0.14, 1.39±.009, 1.31±0.11 and 1.18±0.10 respectively. The mean diameter of intercalated ducts in the same parts was 19.76±0.44μm, 20.6±0.53μm, 20.34±0.49μm and 19.84±0.98μm respectively. The mean number of striated ducts in the right gland ―a‖ and ―b‖ parts, and in the left gland ―a‖ and ―b‖ parts was 0.55±.008, 0.57±.008, 0.80±0.14 and 0.80±0.14 while mean diameter of striated ducts in the right gland ―a‖ and ―b‖ parts, and in the left gland ―a‖ and ―b‖ parts was 49.90±4.70μm, 53.23±2.50μm, 61.68±3.93μm and 57.73±2.85μm respectively. Conclusion: The difference between the mean number and diameter of the ducts of right and left glands was statistically insignificant.